Whole genome sequencing of multidrug resistant Enterobacterales identified in children and their household members within Siem Reap, Cambodia - Singh, SR; Tang, CY; Mao, B; Soeng, S; Ling, CL; Teo, JQ-M; Vonthanak, S; Turner, P; Hsu, LY; Ong, RT-H (Oxford University Press, 2023)
Objectives: To explore the association of recent hospitalization and asymptomatic carriage of multidrug-resistant Enterobacterales (MDRE) and determine the prevailing strains and antibiotic resistance genes in Siem Reap, Cambodia using WGS. Methods: In this cross-sectional study, faecal samples were collected from two arms: a hospital-associated arm consisted of recently hospitalized children (2–14 years), with their family members; and a community-associated arm comprising children in the matching age group and their family members with no recent hospitalization. Forty-two families in each study arm were recruited, with 376 enrolled participants (169 adults and 207 children) and 290 stool specimens collected from participants. The DNA of ESBL- and carbapenemase-producing Enterobacterales cultured from the faecal samples was subject to WGS on the Illumina NovaSeq platform. Results: Of the 290 stool specimens, 277 Escherichia coli isolates and 130 Klebsiella spp. were identified on CHROMagar ESBL and KPC plates. The DNA of 276 E. coli (one isolate failed quality control test), 89 Klebsiella pneumoniae, 40 Klebsiella quasipneumoniae and 1 Klebsiella variicola was sequenced. CTX-M-15 was the most common ESBL gene found in E. coli (n = 104, 38%), K. pneumoniae (n = 50, 56%) and K. quasipneumoniae (n = 16, 40%). The prevalence of bacterial lineages and ESBL genes was not associated with any specific arm. Conclusions: Our results demonstrate that MDRE is likely to be endemic within the Siem Reap community. ESBL genes, specifically blaCTX-M, can be found in almost all E. coli commensals, indicating that these genes are continuously propagated in the community through various unknown channels at present.